Financing the Chek Lap Kok New Airport: A Case Study in Amending the Sino-British Joint Declaration on the Question of Hong Kong - Bennett, Michael S. (Columbia Journal of Asian Law, 1995)
Since the signing in 1984 of the Sino-British Joint Declaration on the Question of Hong Kong (the “Joint Declaration”), a number of issues involving the administration of Hong Kong have caused friction between Great Britain (“Britain”) and the People’s Republic of China (“China”). One of the most contentious of such issues concerns the financing of a new airport in the territory Construction of the airport, which is to be called Chek Lap Kok New Airport, has already begun on outlying Lantau Island. The total cost for completing the airport, and a number of bridges, tunnels and railway lines needed to link the airport to Hong Kong Island, is estimated to be in excess of US$20 billion, making it one of the largest infrastructure projects currently under way in the world.